Development of an epitope-based HIV-1 vaccine strategy from HIV-1 lipopeptide to dendritic-based vaccines. (3rd October 2017) - Surenaud, Mathieu; Lacabaratz, Christine; Zurawski, Gérard; Lévy, Yves; Lelièvre, Jean-Daniel
ABSTRACT: Introduction : Development of a safe, effective and globally affordable Human Immunodeficiency Virus strain 1 (HIV-1) vaccine offers the best hope for future control of the HIV-1 pandemic. However, with the exception of the recent RV144 trial, which elicited a modest level of protection against infection, no vaccine candidate has shown efficacy in preventing HIV-1 infection or in controlling virus replication in humans. There is also a great need for a successful immunotherapeutic vaccine since combination antiretroviral therapy (cART) does not eliminate the reservoir of HIV-infected cells. But to date, no vaccine candidate has proven to significantly alter the natural history of an individual with HIV-1 infection. Areas covered : For over 25 years, the ANRS (France Recherche Nord&Sud Sida-HIV hépatites) has been committed to an original program combining basic science and clinical research developing an epitope-based vaccine strategy to induce a multiepitopic cellular response against HIV-1. This review describes the evolution of concepts, based on strategies using HIV-1 lipopeptides towards the use of dendritic cell (DC) manipulation. Expert commentary : Understanding the crucial role of DCs in immune responses allowed moving from the non-specific administration of HIV-1 sequences with lipopeptides to DC-based vaccines. These DC-targeting strategies should improve HIV-1 vaccine efficacy.